Positive plate and preparation method thereof, battery and electric equipment
By adding porous ceramic materials to the positive electrode sheet of the battery, the diffusion rate of electrolyte and lithium ions is improved, and the problem of difficult to take into account the fast charging performance of the battery when increasing the energy density is solved, achieving both high energy density and fast charging performance.
Patent Information
- Application Number
- CN202411756637.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-11
AI Technical Summary
While the existing batteries increase their energy density, it is difficult to take into account both fast charging performance, resulting in energy density and fast charging performance becoming two performance indicators that restrict each other.
By adding a certain proportion of porous ceramic materials to the positive electrode sheet, the diffusion rate and wetting ability of the electrolyte are improved, and the diffusion rate of lithium ions is increased, thereby improving the fast charging ability under high surface density conditions.
It achieves the rapid charging performance of the battery significantly improved without reducing the energy density, ensuring that the battery has a higher energy density and better fast charging performance.
Smart Images

Figure CN119812216A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet and a preparation method thereof, a battery and an electrical device. Background Art
[0002] With the rapid development of new energy vehicles in China, technologies such as safety, driving range and fast charging have become the priority indicators for consumers to purchase new energy vehicles. At present, the main means to improve energy density is to increase the surface density of battery pole pieces, and improving fast charging capability is mainly to reduce the surface density of pole pieces. Energy density and fast charging performance have become two mutually restrictive performance indicators. How to obtain batteries with high energy density and good fast charging performance is an urgent problem to be solved. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a positive electrode sheet with higher energy density and better fast charging performance, a preparation method thereof, a battery and an electrical device.
[0004] In the first aspect of the present application, a positive electrode sheet is provided. According to an embodiment of the present application, the positive electrode sheet includes a positive electrode current collector; a positive electrode active material layer, the positive electrode active material layer is located on at least one side surface of the positive electrode current collector, and the positive electrode active material layer contains active materials and porous ceramics. In the positive electrode sheet, by adding a certain proportion of porous ceramic materials, the diffusion rate of the electrolyte in the positive electrode sheet can be effectively improved, the wetting and liquid retention ability of the electrolyte on the positive electrode sheet can be improved, and the diffusion rate of lithium ions in the positive electrode sheet is increased. Under the condition of high surface density, the fast charging capability can be significantly improved.
[0005] According to the embodiment of the present application, the porous ceramic is substantially uniformly distributed in the positive electrode active material layer. As a result, the electrolyte infiltration and liquid retention capabilities at various locations in the positive electrode sheet can be substantially consistent, and the lithium ion diffusion rate is also substantially consistent, thereby avoiding problems such as local electrolyte depletion and poor infiltration, thereby facilitating the improvement of the electrochemical performance of the battery using the positive electrode sheet.
[0006] According to an embodiment of the present application, based on the total mass of the positive electrode active material layer, the mass percentage of the porous ceramic is 0.1% to 2%, specifically 0.2% to 1%. Within the above content range, the positive electrode sheet can have a suitable porosity, improve the electrolyte wettability and liquid retention performance of the positive electrode sheet, thereby improving the fast charging performance of the battery using the positive electrode sheet, and basically will not reduce the surface density of the positive electrode sheet, thereby ensuring that the battery using the positive electrode sheet has a higher energy density.
[0007] According to an embodiment of the present application, the D50 particle size D1 of the porous ceramic is 0.5 to 5 times the D50 particle size D2 of the positive electrode active material. When the particle size of the porous ceramic is within the above range, the positive electrode sheet can have a higher surface density while the electrolyte wettability and liquid retention performance are significantly improved, and thus the battery using the positive electrode sheet can have a higher energy density and better fast charging performance.
[0008] According to an embodiment of the present application, the porous ceramic satisfies at least one of the following conditions:
[0009] The D50 particle size D1 of the porous ceramic is 1 to 40 microns, preferably 1 to 20 microns;
[0010] The pore size of the porous ceramic is 1nm to 0.5D1;
[0011] The porosity of the porous ceramic is 10% to 50%;
[0012] The compressive strength of the porous ceramic is 0.2 MPa to 2 MPa, preferably 0.5 MPa to 1 MPa.
[0013] Within the above parameter range, the energy density and fast charging performance of the battery using this positive electrode sheet can be further improved.
[0014] According to an embodiment of the present application, the positive electrode active material layer includes a plurality of sub-active material layers stacked in sequence, the direction close to the positive electrode current collector is defined as the inner side, and the direction away from the positive electrode current collector is defined as the outer side, and the plurality of sub-active material layers meet at least one of the following conditions:
[0015] The D50 particle size of the porous ceramic in the sub-active material layer located on the outside is greater than or equal to the D50 particle size of the porous ceramic in the sub-active material layer located on the inside;
[0016] The content of the porous ceramic in the sub-active material layer located on the outside is greater than or equal to the content of the porous ceramic in the sub-active material layer located on the inside.
[0017] According to an embodiment of the present application, the plurality of sub-active material layers satisfy at least one of the following conditions:
[0018] In the direction from the inside to the outside, the D50 particle size of the porous ceramics in the plurality of sub-active material layers gradually increases;
[0019] The content of the porous ceramic in the plurality of sub-active material layers gradually increases from the inside to the outside.
[0020] According to an embodiment of the present application, the positive electrode active material layer includes a first sub-active material layer and a second sub-active material layer stacked from the inside to the outside, the first sub-active material layer includes a first active material and a first porous ceramic, and the second sub-active material layer includes a second active material and a second porous ceramic.
[0021] According to an embodiment of the present application, the D50 particle size of the first porous ceramic is 1 to 5 μm.
[0022] According to an embodiment of the present application, based on the total mass of the first sub-active material layer, the mass percentage of the first porous ceramic is 0% to 2%, and specifically may be 0.2% to 1%.
[0023] According to an embodiment of the present application, the D50 particle size of the second porous ceramic is 5 to 20 μm.
[0024] According to an embodiment of the present application, based on the total mass of the second sub-active material layer, the mass percentage of the second porous ceramic is 0.1% to 2%, and specifically may be 0.5% to 1%.
[0025] According to an embodiment of the present application, the ratio of the thickness of the first sub-active material layer to the thickness of the second sub-active material layer is 0.5-1:0.5-1, and may be specifically 1:1.
[0026] According to an embodiment of the present application, the D50 particle size of the first active material is 0.5 μm to 2 μm.
[0027] According to an embodiment of the present application, the D50 particle size of the second active material is 1 μm to 4 μm.
[0028] According to an embodiment of the present application, the porous ceramic includes at least one of aluminum oxide, aluminum hydroxide, boron nitride, and silicon oxide.
[0029] According to an embodiment of the present application, the positive electrode sheet further includes a conductive layer, and the conductive layer is located between the positive electrode current collector and the positive electrode active material layer.
[0030] The second aspect of the present application provides a method for preparing the positive electrode sheet described above. According to an embodiment of the present application, the method comprises: coating a positive electrode slurry containing a positive electrode active material and a porous ceramic on at least one side of a positive electrode current collector to form a positive electrode active material layer, thereby obtaining the positive electrode sheet. The solution is simple and convenient, compatible with existing technologies, does not require additional equipment or processes, and is easy to achieve large-scale production.
[0031] According to an embodiment of the present application, the method may further include: coating a conductive slurry containing a conductive agent on at least one side surface of the positive electrode collector to form a conductive layer; coating the positive electrode slurry on the surface of the conductive layer away from the positive electrode collector to form the positive electrode active material layer to obtain the positive electrode sheet.
[0032] In a third aspect of the present application, a battery is provided. According to an embodiment of the present application, the battery comprises the positive electrode sheet described above or the positive electrode sheet prepared by the method described above. The battery has a high energy density and good fast charging performance.
[0033] In a fourth aspect of the present application, an electric device is provided. According to an embodiment of the present application, the electric device includes the battery described above. The electric device has better endurance and better fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the structure of a positive electrode sheet according to an embodiment of the present application.
[0035] Figure 2 It is a schematic diagram of the structure of a positive electrode sheet of another embodiment of the present application.
[0036] Figure 3 It is a schematic diagram of the structure of a positive electrode sheet of another embodiment of the present application.
[0037] Figure 4 It is a schematic diagram of the structure of a positive electrode sheet of another embodiment of the present application.
[0038] Figure 5 It is a schematic diagram of the structure of a positive electrode sheet of another embodiment of the present application.
[0039] Reference numerals:
[0040] 10: positive electrode current collector 20: positive electrode active material layer 21: sub-active material layer 22: first sub-active material layer 22: second sub-active material layer 30: conductive layer DETAILED DESCRIPTION
[0041] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0042] In a first aspect of the present application, a positive electrode sheet is provided. According to an embodiment of the present application, referring to Figure 1 and Figure 2The positive electrode sheet includes: a positive electrode current collector 10; a positive electrode active material layer 20, wherein the positive electrode active material layer 20 is located on at least one side of the positive electrode current collector 10, and the positive electrode active material layer 10 contains active materials and porous ceramics. In the positive electrode sheet, by adding a certain proportion of porous ceramic materials, the diffusion rate of the electrolyte in the positive electrode sheet can be effectively improved, the electrolyte's ability to infiltrate and retain the positive electrode sheet can be improved, and the diffusion rate of lithium ions in the positive electrode sheet can be increased. Under the condition of high surface density, the fast charging capacity can be significantly improved, for example, the speed of 10% SOC to 80% SOC can reach 5min to 10min.
[0043] Specifically, during the use of the battery, the active material has the characteristics of expansion and contraction, which causes the pores in the positive electrode to change all the time, and the electrolyte is constantly squeezed out and absorbed into the positive electrode. Porous ceramics have a certain toughness, and there is no volume change during the charge and discharge process. The electrolyte can be stored in the pores of the ceramic, so that the positive electrode can accommodate more electrolyte and improve the fast charging performance.
[0044] According to an embodiment of the present application, the porous ceramic is basically evenly distributed in the positive electrode active material layer. It can be understood that, ideally, the porous ceramic is completely evenly distributed in the positive electrode active material layer, but due to various factors such as process limitations and errors, porous ceramics are generally unable to be completely evenly distributed. The description method used in this article "basically evenly distributed" includes the situation of completely evenly distributed, and also includes the situation where the distribution of porous ceramics fluctuates within a reasonable range due to process limitations, errors, etc. This arrangement can make the electrolyte infiltration and liquid retention capabilities at various positions in the positive electrode sheet basically consistent, and the lithium ion diffusion rate is also basically consistent, avoiding problems such as local electrolyte depletion and poor infiltration, thereby helping to improve the electrochemical performance of the battery using the positive electrode sheet.
[0045] It can be understood that porous ceramics are ceramic materials with a large number of pore structures, and these pores can be interconnected or closed. As an example, the porous ceramics used in some embodiments of the present application have an open porous structure, which is conducive to improving the electrolyte wetting performance and liquid retention performance of the positive electrode sheet. In other embodiments, the porous ceramic can be a solid structure or a hollow structure. As an example, the porous ceramic has a hollow structure, which can further improve the electrolyte wetting performance and liquid retention performance of the positive electrode sheet.
[0046] According to the embodiments of the present application, the larger the particle size of the porous ceramic, the more pores can be formed in the positive electrode sheet, and the surface density of the positive electrode active material layer will also be reduced, thereby reducing the energy density of the battery using the positive electrode sheet. Taking into account the fast charging performance and energy density of the battery, the D50 particle size D1 of the porous ceramic is 0.5 to 5 times the D50 particle size D2 of the positive electrode active material, such as 0.5 times, 1 times, 1.5 times, 2 times, 2.5 times, 3 times, 3.5 times, 4 times, 4.5 times, 5 times, etc. The particle size of the porous ceramic is within the above range, which can make the positive electrode sheet have a higher surface density while the electrolyte wettability and liquid retention performance are significantly improved, so that the battery using the positive electrode sheet can have a higher energy density and better fast charging performance.
[0047] According to an embodiment of the present application, the D50 particle size D1 of the porous ceramic may be 1 to 40 microns, specifically 1 to 20 microns, more specifically 1 micron, 2 microns, 5 microns, 8 microns, 10 microns, 12 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns, etc. Within the above range, the energy density and fast charging performance of the battery using the positive electrode sheet can be further improved.
[0048] Herein, D50 particle size is also called median particle size or volume average particle size, which is the particle size corresponding to 50% of the cumulative volume of the material. Its physical meaning is that the sum of the volumes of all particles smaller than D50 is equal to the sum of the volumes of all particles larger than D50. It can be detected by conventional methods in the art, for example, by a laser particle size analyzer.
[0049] According to the embodiments of the present application, the pore size of the porous ceramic is 1nm to 0.5D1, such as 1nm, 5nm, 10nm, 0.1D1, 0.2D1, 0.3D1, 0.4D1, 0.5D1, etc. The above pore size is conducive to improving the porosity of the positive electrode active material layer, thereby improving the electrolyte wetting performance and liquid retention performance of the positive electrode sheet. When the positive electrode sheet is used in a battery, the fast charging performance can be effectively improved without substantially reducing the energy density.
[0050] Herein, the pore size of porous ceramics refers to the diameter of the pores in the porous ceramics, usually the maximum diameter of the pores, which can be detected by conventional methods in the art, such as gas adsorption, scanning electron microscopy, transmission electron microscopy, etc.
[0051] According to an embodiment of the present application, the porosity of the porous ceramic is 10% to 50%, specifically 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. With the above porosity, the porosity of the positive electrode sheet can be effectively improved, thereby improving the electrolyte wettability and liquid retention of the positive electrode sheet, while maintaining a certain mechanical strength of the porous ceramic.
[0052] Herein, the porosity of porous ceramics refers to the ratio of the pore volume to the total volume of the porous ceramics, which can be detected by conventional methods in the art, such as density method, gas adsorption method, fluid filling method, etc.
[0053] According to the embodiments of the present application, the compressive strength of the porous ceramic is 0.2Mpa to 2Mpa, specifically 0.5Mpa to 1Mpa, more specifically 0.2Mpa, 0.5Mpa, 0.8Mpa, 1Mpa, 1.2Mpa, 1.5Mpa, 1.8Mpa, 2Mpa, etc. With the above compressive strength, the pore structure can be well maintained, the performance requirements of the rolling process and the like in the preparation process of the positive electrode sheet can be met, and it is not easy to break.
[0054] In this article, the compressive strength of porous ceramics is an important indicator of its mechanical properties, which refers to the ability of porous ceramics to resist destruction under force. Specifically, it can be the force / ceramic material surface area when the porous ceramics are crushed under pressure. It can be tested by methods such as a pressure testing machine or a universal testing machine.
[0055] According to the embodiments of the present application, the shape of the porous ceramic is not particularly limited, and can be spherical, polygonal, unequal-sided, regular or irregular geometric shapes, etc., and the present application has no particular restrictions. The shape of the pores in the porous ceramic is also not particularly limited, as long as it can accommodate the electrolyte.
[0056] According to an embodiment of the present application, the porous ceramic includes at least one of aluminum oxide, aluminum hydroxide, boron nitride, and silicon oxide. Therefore, the material source is wide, easy to obtain, low in cost, and has good compatibility with other substances in the positive electrode active material layer.
[0057] According to an embodiment of the present application, based on the total mass of the positive electrode active material layer, the mass percentage of the porous ceramic is 0.1% to 2%, specifically 0.2% to 1%, and more specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc. Within the above content range, the positive electrode sheet can have a suitable porosity, improve the electrolyte wettability and liquid retention performance of the positive electrode sheet, and thus improve the fast charging performance of the battery using the positive electrode sheet, and basically will not reduce the surface density of the positive electrode sheet, thereby ensuring that the battery using the positive electrode sheet has a higher energy density.
[0058] According to the embodiments of the present application, the positive electrode active material layer can be a single-layer structure or a multi-layer structure. It can be understood that in the positive electrode sheet with a single-layer positive electrode active material layer, the same or different ceramic sizes can be used to improve the porosity of the electrode sheet and increase the liquid absorption performance of the positive electrode sheet. In the positive electrode sheet with a multi-layer positive electrode active material layer, based on the particle size of the active material in each sub-active material layer, the porous ceramic particle size can be distributed in a gradient in the thickness direction of the electrode, that is, in the apparent distribution of the electrode, different pore gradients are formed inside and outside, and the content of porous ceramics in different sub-active material layers can be adjusted to obtain a multi-layer positive electrode sheet with different pores.
[0059] In some embodiments, reference Figure 3 , the positive electrode active material layer 20 includes a plurality of sub-active material layers 21 stacked in sequence, the direction close to the positive electrode current collector 10 is defined as the inner side, and the direction away from the positive electrode current collector 10 is defined as the outer side, and the plurality of sub-active material layers 21 meet at least one of the following conditions: the D50 particle size of the porous ceramic in the sub-active material layer located on the outer side is greater than or equal to the D50 particle size of the porous ceramic in the sub-active material layer located on the inner side; the content of the porous ceramic in the sub-active material layer located on the outer side is greater than or equal to the content of the porous ceramic in the sub-active material layer located on the inner side. As a result, the porosity in the positive electrode active material layer on the outer side is larger, and it is easier for the electrolyte to infiltrate the positive electrode sheet, thereby improving the electrolyte wettability and liquid retention of the positive electrode sheet, and thus improving the fast charging performance of the battery using the positive electrode sheet.
[0060] In some embodiments, the plurality of sub-active material layers satisfy at least one of the following conditions: the D50 particle size of the porous ceramics in the plurality of sub-active material layers gradually increases from the inside to the outside; the content of the porous ceramics in the plurality of sub-active material layers gradually increases from the inside to the outside. Thus, the electrolyte wettability and liquid retention of the positive electrode sheet can be further improved, thereby improving the fast charging performance of the battery using the positive electrode sheet.
[0061] According to the embodiments of the present application, referring to Figure 4 The positive electrode active material layer 20 includes a first sub-active material layer 201 and a second sub-active material layer 202 stacked from the inside to the outside, the first sub-active material layer 201 includes a first active material and a first porous ceramic, and the second sub-active material layer 202 includes a second active material and a second porous ceramic.
[0062] In some embodiments, the D50 particle size of the first porous ceramic is 1 to 5 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc.
[0063] In some embodiments, based on the total mass of the first sub-active material layer, the mass percentage of the first porous ceramic is 0% to 2%, specifically 0.2% to 1%, and more specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc.
[0064] In some embodiments, the D50 particle size of the second porous ceramic is 5 to 20 μm, specifically 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc.
[0065] In some embodiments, based on the total mass of the second sub-active material layer, the mass percentage of the second porous ceramic is 0.1% to 2%, specifically 0.5% to 1%, and more specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, .2%, .3%, .4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc.
[0066] In some embodiments, the D50 particle size of the first active material is 0.5 μm to 2 μm, specifically 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, etc.
[0067] In some embodiments, the D50 particle size of the second active material is 1 μm to 4 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc.
[0068] The porous ceramics and active materials in the first active material layer and the second active material layer fully meet the above conditions, so that the positive electrode sheet has good electrolyte wettability and liquid retention while having a high surface density, thereby making the battery using the positive electrode sheet have a higher energy density and better fast charging performance.
[0069] In some embodiments, the ratio of the thickness of the first sub-active material layer to the thickness of the second sub-active material layer is 0.5-1:0.5-1, specifically 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 2:1, etc., specifically 1:1. Thus, the energy density and fast charging performance of the battery using the positive electrode sheet can be further improved.
[0070] According to the embodiments of the present application, the specific type of positive electrode active material in the positive electrode active material layer can be selected according to actual needs. In some embodiments, the positive electrode active material includes but is not limited to lithium transition metal oxides and / or lithium phosphates containing olivine structures. Specifically, the lithium transition metal oxides include lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides (such as NCM333, NCM523, NCM211, NCM622, NCM811), lithium nickel cobalt aluminum oxides (such as LiNi 0.85 Co 0.15 Al 0.05 O2) or a combination thereof; olivine-structured lithium-containing phosphates include but are not limited to lithium iron phosphate (such as LiFePO4), lithium iron manganese phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate (such as LiMn x Fe 1-x PO4, 0<x<1), at least one of a composite material of lithium manganese iron phosphate and carbon.
[0071] It can be understood that, in addition to the positive electrode active material and porous ceramics mentioned above, the positive electrode active material layer may also include a binder and a conductive agent.
[0072] In some embodiments, the positive electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, which is not limited in the embodiments of the present application.
[0073] In some embodiments, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA) and carboxymethyl chitosan (CMCS).
[0074] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0075] According to the embodiments of the present application, referring to Figure 5 The positive electrode sheet further includes a conductive layer 30, and the conductive layer 30 is located between the positive electrode current collector 10 and the positive electrode active material layer 20. Thus, the conductivity of the positive electrode sheet can be effectively improved, thereby improving the electrochemical performance of the battery using the positive electrode sheet.
[0076] According to an embodiment of the present application, a conductive agent and a binder may be included in the conductive layer. As an example, the conductive agent may include but is not limited to graphite or other carbon materials, such as superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and one or more of carbon nanofibers. As an example, the binder may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA) and carboxymethyl chitosan (CMCS).
[0077] The second aspect of the present application provides a method for preparing the positive electrode sheet described above. According to an embodiment of the present application, the method comprises: coating a positive electrode slurry containing a positive electrode active material and a porous ceramic on at least one side of a positive electrode current collector to form a positive electrode active material layer, thereby obtaining the positive electrode sheet. The solution is simple and convenient, compatible with existing technologies, does not require additional equipment or processes, and is easy to achieve large-scale production.
[0078] According to an embodiment of the present application, the positive electrode active material, porous ceramic, conductive agent and binder can be added to a solvent to obtain a positive electrode slurry, which is then coated on at least one side of the positive electrode collector, and then dried and rolled to obtain a positive electrode sheet.
[0079] It can be understood that when the positive electrode active material layer has a single-layer structure, only one slurry needs to be prepared and applied sequentially. When the positive electrode active material layer has a multi-layer structure, one slurry can be prepared and applied multiple times to form the positive electrode active material layer; or multiple slurries can be prepared according to the formula of different sub-active material layers, and applied multiple times (such as applying one slurry each time) to form the positive electrode active material layer.
[0080] This application innovatively applies porous ceramics to positive electrode sheets. The porous ceramics are dispersed together with active materials, binders, and conductive agents during the electrode slurrying process, and the required positive electrode sheets are made through a coating process, which is suitable for high energy density and fast charging batteries.
[0081] According to an embodiment of the present application, the method may further include: coating a conductive slurry containing a conductive agent on at least one side surface of the positive electrode collector to form a conductive layer; coating the positive electrode slurry on the surface of the conductive layer away from the positive electrode collector to form the positive electrode active material layer to obtain the positive electrode sheet.
[0082] Specifically, the conductive agent and the binder can be added to a solvent to prepare a conductive slurry, and then the conductive slurry is first coated on at least one side of the positive electrode current collector, and then the positive electrode active material layer is formed by coating the surface of the conductive layer away from the current collector. The coating of the positive electrode active material layer is consistent with the previous description and will not be elaborated here.
[0083] In a third aspect of the present application, a battery is provided. According to an embodiment of the present application, the battery comprises the positive electrode sheet described above or the positive electrode sheet prepared by the method described above. The battery has a high energy density and good fast charging performance.
[0084] It can be understood that there is no other limitation on the specific type of the battery, including but not limited to lithium-ion batteries, sodium-ion batteries, etc., and the battery can be a square shell battery, a soft pack battery, a cylindrical battery, etc., and can be in different forms such as a battery cell, a battery module, a battery pack, etc.
[0085] It can also be understood that in addition to the positive electrode sheet described above, the battery may also include other necessary structures and components of conventional batteries. Taking a lithium-ion battery as an example, it may include an outer package, and an electrode assembly and an electrolyte contained in the outer package, and the electrode assembly may include a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet.
[0086] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0087] In some embodiments, the negative electrode active material may include one or more of a carbon-based material, a silicon-based material, a tin-based material, and lithium titanate. The carbon-based material may include one or more of graphite (e.g., artificial graphite, natural graphite, etc.), soft carbon, and hard carbon. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys.
[0088] In some embodiments, the negative electrode film layer may include a negative electrode binder. As an example, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS), and the embodiments of the present application are not limited thereto.
[0089] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, which is not limited in the present embodiment.
[0090] In some embodiments, the electrolyte may include an electrolyte salt, and the electrolyte salt may include at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium difluorophosphate, lithium difluorobis(oxalatophosphate), and lithium tetrafluoroborate.
[0091] In some embodiments, the organic solvent in the electrolyte may include one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl formate, ethyl acetate, methyl acetate, fluoroethylene carbonate, difluoroethylene carbonate, fluoroethyl methyl carbonate, fluorodiethyl carbonate, ethyl fluoroformate, fluoroethyl acetate, and fluoromethyl acetate.
[0092] In some embodiments, the diaphragm may include but is not limited to a single-layer or multi-layer polymer diaphragm, such as a polyethylene diaphragm, a polypropylene diaphragm, a polyethylene-polypropylene composite diaphragm, and the like.
[0093] In a fourth aspect of the present application, an electric device is provided. According to an embodiment of the present application, the electric device includes the battery described above. The electric device has better endurance and better fast charging performance.
[0094] According to an embodiment of the present application, the power-consuming device may include a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc., but is not limited thereto. The battery may be used as a power source for the power-consuming device, or may be used as an energy storage unit for the power-consuming device.
[0095] It can be understood that in addition to the battery mentioned above, the electrical equipment may also include necessary structures and components of conventional electrical equipment. Taking electric vehicles as an example, they may include necessary structures and components such as body, windows, chassis, engine, seats, tires, etc., which will not be elaborated here.
[0096] The embodiments of the present application are described in detail below.
[0097] Embodiment 1:
[0098] Conductive coating is applied on the surface of the current collector: the positive electrode conductive slurry (the mass ratio of carbon black, CMC and binder PVDF in the slurry is 100:6:20) is evenly applied on the aluminum foil to form a conductive layer with a thickness of 2 μm;
[0099] Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate, conductive agent carbon black, binder PVDF, and porous ceramic are dispersed in NMP solvent in a certain proportion to obtain a uniformly mixed positive electrode slurry; the positive electrode slurry is evenly coated on the above conductive layer, and after baking and cutting, the positive electrode sheet is obtained; the coating amount is 450g / m 2 , the thickness of the positive electrode sheet is 186μm;
[0100] Preparation of negative electrode sheet: Disperse the negative electrode active material graphite, conductive agent carbon black, thickener CMC, and binder SBR in deionized water at a mass ratio of 95:1:2:2, and stir to mix evenly to obtain negative electrode slurry. Apply the slurry evenly on copper foil, bake and cut to obtain negative electrode sheet; the amount of coating is 205g / m 2 , compacted density 1.54g / cm 3 , the thickness of the negative electrode sheet is 140μm.
[0101] Battery assembly: According to the stacking method, the negative electrode sheet, the separator (PE single-sided adhesive separator (base film 9μm, coating 2μm)), and the positive electrode sheet are stacked in sequence to make a soft-pack battery. After injecting the electrolyte (solvent EC+EMC+DEC, lithium salt lithium hexafluorophosphate, 1.0mol / L), it is activated by formation and then tested.
[0102] Embodiments 2, 5 to 8, 10 to 15
[0103] Same as Example 1, differences are shown in Table 1.
[0104] Example 3
[0105] Same as Example 1, except that:
[0106] Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate, the conductive agent carbon black, the binder PVDF, and the porous ceramic are dispersed in NMP solvent according to a certain proportion to obtain a uniformly mixed first positive electrode slurry; the first positive electrode slurry is uniformly coated on the above conductive layer and baked; the positive electrode active material lithium iron phosphate, the conductive agent carbon black, the binder PVDF, and the porous ceramic are dispersed in NMP solvent according to a certain proportion to obtain a uniformly mixed second positive electrode slurry; the second positive electrode slurry is uniformly coated on the coating formed by the above first positive electrode slurry, and after baking and cutting, the positive electrode sheet is obtained; the coating amount is 450g / m 2 , the thickness of the positive electrode sheet is 186μm.
[0107] Embodiments 4, 9, and 16
[0108] Same as Example 3, differences are shown in Table 1.
[0109] Comparative Examples 1-2
[0110] Same as Example 1, differences are shown in Table 1.
[0111] Table 1
[0112]
[0113]
[0114] Note: In Examples 3, 4, 9 and 16 in Table 1, the positive electrode sheet has a double-layer positive electrode active material layer. The data before and after the " / " in the description "94.8:1:2:2:0.2 / 94.5:1:2:2:0.5" respectively represent the corresponding data in the two positive electrode active material layers in the direction away from the positive electrode current collector. Other similar descriptions have the same meaning.
[0115] Performance testing:
[0116] 1. Energy density test: At 25°C, charge to 3.8V at C / 3 constant current, charge to 3.8V at 0.1C, and leave for 5 minutes; discharge to 2.0V at C / 3 constant current. Energy density = discharge energy / cell weight. See Table 2 for test results.
[0117] 2. Fast charging time: The three-electrode method (lithium sheet as three electrodes) is used to measure the lithium potential, and then the fast charging time is calculated based on the lithium potential. The test results are shown in Table 2.
[0118] 3. D50 particle size: tested by laser particle size analyzer, refer to GB / T19077-2016.
[0119] 4. Porous ceramic pore size and porosity: The pore size is detected by SEM, and the porosity is detected by mercury intrusion method, referring to GB / T21650.
[0120] 5. Compressive strength of porous ceramics: tested in accordance with GB / T 8489-2006.
[0121] Table 2
[0122]
[0123]
[0124] It can be clearly seen from the above data that after adding porous ceramics, the energy density of the battery is almost unaffected, but the fast charging performance is significantly improved.
[0125] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0126] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0127] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A positive electrode sheet, characterized in that: include: Positive electrode current collector; A positive electrode active material layer is located on at least one side of the positive electrode current collector, and the positive electrode active material layer contains active materials and porous ceramics.
2. The positive electrode sheet according to claim 1, characterized in that: The porous ceramic is substantially uniformly distributed in the positive electrode active material layer.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: Based on the total mass of the positive electrode active material layer, the mass percentage of the porous ceramic is 0.1% to 2%, preferably 0.2% to 1%.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The D50 particle size D1 of the porous ceramic is 0.5 to 5 times the D50 particle size D2 of the positive electrode active material.
5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The porous ceramic satisfies at least one of the following conditions: The D50 particle size D1 of the porous ceramic is 1 to 40 microns, preferably 1 to 20 microns; The pore size of the porous ceramic is 1nm to 0.5D1; The porosity of the porous ceramic is 10% to 50%; The compressive strength of the porous ceramic is 0.2Mpa to 2Mpa, preferably 0.5Mpa to 1Mpa.
6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The positive electrode active material layer includes a plurality of sub-active material layers stacked in sequence, with the direction close to the positive electrode current collector being defined as the inner side and the direction away from the positive electrode current collector being defined as the outer side, and the plurality of sub-active material layers satisfying at least one of the following conditions: The D50 particle size of the porous ceramic in the sub-active material layer located on the outside is greater than or equal to the D50 particle size of the porous ceramic in the sub-active material layer located on the inside; The content of the porous ceramic in the sub-active material layer located on the outside is greater than or equal to the content of the porous ceramic in the sub-active material layer located on the inside.
7. The positive electrode sheet according to claim 6, characterized in that: The plurality of sub-active material layers satisfy at least one of the following conditions: In the direction from the inside to the outside, the D50 particle size of the porous ceramics in the plurality of sub-active material layers gradually increases; The content of the porous ceramic in the plurality of sub-active material layers gradually increases from the inside to the outside.
8. The positive electrode sheet according to claim 6, characterized in that: The positive electrode active material layer includes a first sub-active material layer and a second sub-active material layer stacked from the inside to the outside, the first sub-active material layer includes a first active material and a first porous ceramic, the second sub-active material layer includes a second active material and a second porous ceramic, and satisfies at least one of the following conditions: The D50 particle size of the first porous ceramic is 1 to 5 μm; Based on the total mass of the first sub-active material layer, the mass percentage of the first porous ceramic is 0% to 2%, preferably 0.2% to 1%; The D50 particle size of the second porous ceramic is 5 to 20 μm; Based on the total mass of the second sub-active material layer, the mass percentage of the second porous ceramic is 0.1% to 2%, preferably 0.5% to 1%; The ratio of the thickness of the first sub-active material layer to the thickness of the second sub-active material layer is 0.5-1:0.5-1, preferably 1:1; The D50 particle size of the first active material is 0.5 μm to 2 μm; The D50 particle size of the second active material is 1 μm to 4 μm.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The porous ceramic includes at least one of aluminum oxide, aluminum hydroxide, boron nitride and silicon oxide.
10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The invention also includes a conductive layer, wherein the conductive layer is located between the positive electrode current collector and the positive electrode active material layer.
11. A method for preparing the positive electrode sheet according to any one of claims 1 to 10, characterized in that: include: A positive electrode slurry containing a positive electrode active material and porous ceramics is coated on at least one side of a positive electrode current collector to form a positive electrode active material layer, thereby obtaining the positive electrode sheet.
12. The method according to claim 11, characterized in that include: Applying a conductive slurry containing a conductive agent on at least one side of the positive electrode current collector to form a conductive layer; The positive electrode slurry is coated on the surface of the conductive layer away from the positive electrode current collector to form the positive electrode active material layer, thereby obtaining the positive electrode sheet.
13. A battery, characterized in that: The invention comprises the positive electrode sheet according to any one of claims 1 to 10 or the positive electrode sheet prepared by the method according to claim 11 or 12.
14. An electrical device, characterized in that: Comprising the battery of claim 13.
Citation Information
Patent Citations
Positive pole piece, secondary battery and electronic device
CN116111042A
Positive pole piece, secondary battery and electric device
CN116344741A
Negative pole piece, energy storage device and electric equipment
CN116525761A
Positive plate and battery
CN116799143A
Electrode and lithium ion battery
CN116845246A